LITERATURE REVIEW : Teknik Hold-Relax Untuk Meningkatkan Fleksibilitas Otot Hamstring - Viola Arsita Errendyar (2020)
Almost all human activities are affected by motion. Physical condition is one important factor in carrying out daily activities. One of the physical conditions is determined bymuscle flexibility. Stretching is done to increase ROM, increase joint muscle flexibility and prevent the risk of injury. The purpose of this study was to systematically examine the effect of the application of the Hold-Relax stretching technique to the increased flexibility of the hamstring muscles. The literary method used is the Literature Study. Based on the literature search results there are 5 literatures. 3 literature came from Google Scholar, 1 literature came from Research Gate, and 1 literature came from Semantic Scholar. As a result, the Hold-Relax Technique is effective in increasing the flexibility of the hamstring muscles. When compared with other stretching techniques (SS, MTSLR and other PNF techniques), the Hold-Relax technique is just as effective. With the PNF Hold-Relax stretching technique there will be an increase in the flexibility of the hamstring muscles, therefore the Hold-Relax technique can be used to improve one's physical condition in their daily activities. Still need a lot of other literature that uses subjects with hamstring hypomobility, only male or female sex. Using the same measurement methods and instruments are still needed.